Measuring Nurses' Contribution to Care and Outcomes is a Patient Safety Issue. Issue 5 (September 2020) - Simpson, Kathleen Rice
Abstract : Ability to accurately and reliably measure nursing care and link with patient outcomes is a safety issue. The type and dose of nursing care that is required for optimal outcomes must be established as part of the body of evidence to support safe nurse staffing. More work is needed to identify nurse-sensitive measures in maternity, neonatal, and pediatric nursing settings.